Parallel execution of SVM using Symmetrical Multi-Processor (LIBSVM-OMP) - Md Salleh N.S.; Bin Mohamad Shariff A.S.; Bin Kamsani M.I.A.; Nazeri S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application programming interfaces (API); Benchmarking; Diagnosis; Multiprocessing systems; Parallel processing systems; Pattern recognition; Search engines; World Wide Web; Computational problem; MNIST dataset; Multi-processing; OpenMP; Parallel executions; Pattern classification techniques; Performance analysis; Symmetric multi-processors; Support vector machines